Three conductance classes of nicotinic acetylcholine receptors are expressed in developing amphibian skeletal muscle - Owens, JL (J Neurosci, 1989)
Two previously described classes of nicotinic AChRs in vertebrate skeletal muscle have conductances of 40 and 60 pS. In addition, a third conductance class of AChR channels is present in developing Xenopus muscle. This class appears to represent an independent channel type, rather than a subconductance state of the larger conductance channels. The channel has a slope conductance of 25 pS and a reversal potential of about 0 mV membrane potential. Its kinetic properties resemble those of the 40 pS channels present in early embryonic myotomal muscle. The channel has a mean open time of about 6 msec (at 40 mV applied potential). The open time is dependent on membrane potential and increases e-fold for every 60 mV of hyperpolarization. Consecutive openings were often separated by brief closures of about 0.4 msec in duration. The identity of the channel as a nicotinic AChR was established by blocking the channel openings with alpha-BTX and by demonstrating bursting and desensitization in the presence of high agonist concentrations. In some muscles (e.g., extraocular), this channel may be a predominant form at early developmental stages and could therefore be important to the function of developing synapses in those muscles.